Influence of Macro Synthetic Fibers on the Flexural Behavior of Reinforced Concrete Slabs with Opening - Rajai Z. Al-Rousan (Civil Engineering Journal, 2022)
In this study, the flexural behavior of one-way RC slabs after adding the macro discontinuous structural synthetic fiber (DSSF) under different opening sizes is investigated. Based on the previously conducted research, the 0.55 DSSF percentage was utilized since it was reported as the optimum value for enhancing the slab's performance. Moreover, further increases in the DSSF percentages proved to have the same improvement obtained by the 0.55%. Experimental testing was carried out on sixty-four one-way slabs under the effects of square opening existence (with or without), heat levels of 20, 200, 400, and 600 °C, and opening sizes of 100, 150, and 200 mm. The opening was created at the maximum bending moment region at the slab's center between the two loading points. For comparison purposes, the tested slabs were divided into main groups based on the DSSF existence. It was found that the resulted improvement by adding the DSSF material is affected by the size of the created opening. Furthermore, results revealed an increasing linear relationship between the applied load and the deflection and between the longitudinal concrete strain and the steel reinforcement. Besides, duplicating the opening size enhances the ductility index value by a maximum improvement percentage of 13% under an opening size ratio of less than 4.5%, while the improvement percentage becomes less under a further increase in the opening size ratio. Moreover, initial stiffness is more affected by increasing the temperature values twice those recorded for the yielding stiffness. Doi: 10.28991/CEJ-2022-08-09-016 Full Text: PDF